A unified approach to evaluate axial force-moment interaction curves of concrete encased steel composite columns. (15th December 2019) - Lai, Binglin; Liew, J.Y. Richard; Hoang, An Le; Xiong, Mingxiang
Highlights: A database is collected for concrete encased steel composite columns under various loading types. The applicability of EN 1994-1-1 for concrete encased steel composite columns is evaluated. Sensitivity study is performed to assess the accuracy of EC4 method. An analytical procedure is developed to construct the axial force-bending moment diagrams. A unified design method is proposed to construct the interaction diagrams. Abstract: This paper presents a unified approach to evaluate the axial force and moment interaction strength curve of Concrete Encased Steel (CES) composite columns made of different steel and concrete grades. A database was established by collecting the test results of CES composite columns in the literature covering concrete compressive strength ranging from 20 to 104 MPa and steel yield strength from 280 to 913 MPa. A sensitivity study was then carried out to investigate the effect of different design parameters on the accuracy of the current design method EN 1994-1-1 in predicting the ultimate strength of CES composite columns. These design parameters include characteristic strength of materials, steel contribution ratio, concrete cover thickness ratio, longitudinal reinforcement ratio, and volumetric ratio of transverse reinforcement. Analytical study was performed through a self-compiled computer program which was developed based on materials strain compatibility principle. The comparison between the analytical results and test results confirms the validity of the proposed method to provide reasonable prediction of cross-sectional axial-moment interaction curves for CES columns for a wide range of steel and concrete grades. The existing EC4 method, which is based on plastic design principle, was found to be un-conservative in predicting the cross section resistance of CES composite columns with high strength concrete and high strength steel. Further enhancement was made to the proposed method to include both the strain gradient effect and concrete confinement effect to achieve a better agreement with the test results reported in literature. Finally, a simplified method was proposed to construct the axial-moment interaction curves of CES columns, which can be used as a unified approach to design such columns with normal and high strength steel and concrete materials.